Students Difficulties of Solving Inequalities in Calculus - Denbel, Dejene Girma (American Scientific Research Journal for Engineering, Technology, and Sciences, 2013)
The study tries to analyze the students’ difficulties and explore the errors done by the students when finding solution sets for inequalities. For these purpose a test was given to college of natural and computational science students who have taken calculus I or applied mathematics I course in Dilla University, Ethiopia. The results showed that the students are not successful in solving inequalities. The mostly observed mistake was to multiply both sides of inequality by expression that includes variable without paying attention to the sign of this expression. Moreover, significant number of procedural and technical errors is made by the students.